2016
DOI: 10.1111/resp.12800
|View full text |Cite
|
Sign up to set email alerts
|

TNF and IL‐1β exposure increases airway narrowing but does not alter the bronchodilatory response to deep inspiration in airway segments

Abstract: Background and objective: While chronic inflammation of the airway wall and the failure of deep inspiration (DI) to produce bronchodilation are both common to asthma, whether pro-inflammatory cytokines modulate the airway smooth muscle response to strain during DI is unknown. The primary aim of the study was to determine how an inflammatory environment (simulated by the use of pro-inflammatory cytokines) alters the bronchodilatory response to DI. Methods: We used whole porcine bronchial segments in vitro that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Despite the presence of alveolar edema and bronchoconstriction, these alterations were not sufficient to impair blood gases and lung mechanics. Bronchoconstriction might be explained by increased airway narrowing due to circulating proinflammatory cytokines [ 45 ]. In patients with brain injury, bronchoconstriction with increased airway resistance is common [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the presence of alveolar edema and bronchoconstriction, these alterations were not sufficient to impair blood gases and lung mechanics. Bronchoconstriction might be explained by increased airway narrowing due to circulating proinflammatory cytokines [ 45 ]. In patients with brain injury, bronchoconstriction with increased airway resistance is common [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous data showed that IL-1β knockout or receptor blockade abolished an increase of AHR in mice with severe diet-induced obesity 6 . Furthermore, IL-1β may directly potentiate cholinergic bronchoconstriction 12 . There was no signs of eosinophilic or neutrophilic inflammation in BAL associated with obese asthma 13 , 14 and there was no increase in TH2 cytokines like IL-4.…”
Section: Discussionmentioning
confidence: 99%
“…According to results from isolated airway smooth muscle measurements [3], when a critical threshold of strain (3.3%) was exceeded, contractile force in an activated muscle could be significantly reduced for a prolonged period of time. The results from activated airway segments subject to pressure oscillation also indicated the existence of such a threshold, which, when exceeded, abrupt bronchodilation occurred [4]. The strain in airway smooth muscle when lung volume increases from FRC to TLC estimated from the studies reviewed by Boss e on average is much greater than the critical threshold of 3.3%, suggesting that the bronchodilatory effect of deep inspiration observed in healthy human subjects [5,6] may be related to the loss of contractility in airway smooth muscle.…”
mentioning
confidence: 86%